Innovation through collaboration - Beyerlein, Michael Martin; Beyerlein, Susan T.; Kennedy, Frances A. (Advances in interdisciplinary studies of work teams, 2006)
Innovation has become one of the primary core competencies of effective organizations. It leads to changes in products, services, organizational design, processes, strategies, and the systems that support them. It occurs when someone has an idea, shares it with others, and all find ways to turn the idea into action. The sharing is a critical step. Creative ideas blossom in a collaborative environment. Implementation depends on collaboration. The chapters in this volume explore a variety of methods and settings that show how collaboration can be utilized to enable and enhance innovation. The innovation may be incremental or breakthrough and evident at any level of organization: team, community of practice, project or program, company, joint venture, alliance, partnership, or supply chain. In this volume, we refer to high quality interaction in the social network as collaboration. We believe creating the context for effective collaboration is a core competency of the organization. Working together well involves deepening trust among members and sharing ideas, perspectives, energy, and knowledge to address organizational challenges and opportunities. As innovation becomes the key to competitive advantage at company, supply chain, and regional levels, a shift from silos to collaboration becomes essential collaborating across boundaries becomes critical. World class levels of performance are impossible without mastery of collaborative methods, processes, and designs. Few companies have mastered the discipline of collaboration well enough to achieve the highest levels of performance. Inter-agency collaboration in government is equally challenging. The chapters in this volume explore collaborative approaches to innovation and the mechanisms and tools that contribute to the quality of collaborative effort. It discusses the importance of collaborative environments to improve innovation; and addresses how to create a collaborative environment within an organization.